Possible roles for folic acid in the regulation of trophoblast invasion and placental development in normal early human pregnancy - Williams, Paula J.; Bulmer, Judith N.; Innes, Barbara A.; Broughton Pipkin, Fiona (Society for the Study of Reproduction, 2011)
In addition to its role in the prevention of neural tube defects, folic acid has many other physiological functions, including cell proliferation, DNA replication, and antioxidant protection. The aim of this study was to determine the role that folic acid has in regulating placental trophoblast development. Placental explants from placentae at gestational age 7 wk (n ¼ 3) were cultured in folic acid at concentrations of 106 M, 108 M, and 1010 M. Extravillous trophoblast (EVT) invasion was assessed following 6-day culture, and explants were used for immunohistochemical evaluation of proliferation (MKI67) and apoptosis (active caspase 3). In addition, an array was performed on cell culture supernatants to examine a range of matrix metalloproteinases (MMPs) and tissue inhibitors of MMPs (TIMPs). Folic acid increased the invasion of EVT cells in this explant model by between 83% and 19% (P ¼ 0.005), and this was associated with increased MKI67 positivity and decreased active caspase 3 positivity; this effect was concentration dependent and showed a biphasic response. In addition, culture in folic acid increased vascular density, as determined by anti-CD31 immunostaining (P ¼ 0.05). The increase in EVT invasion correlated with increased placental explant secretion of MMP2 (P ¼ 0.01), MMP3 (P¼0.01), and MMP9 (P¼0.02). This study demonstrates that folic acid is potentially important in a number of crucial early stages of placental development, including EVT invasion, angiogenesis, and secretion of MMPs, and highlights the need for further studies to address the benefit of longer-term folic acid supplementation throughout pregnancy to prevent pregnancy disorders associated with deficient placental development, including preeclampsia.